Cross-border freight movement between Thailand-Malaysia-Singapore : utilising border based dry ports for effective inland transaction - Jeevan, Jagan (Array, 2021)
Trade plays an important role in economic growth. Thence, a smooth cross-border transaction between Thailand-Malaysia-Singapore provides a significant implication in international trade. Currently, cross-border transactions face several issues during the crossing of borders between countries and, specifically, happens during the transactions of cargo. A very rigid documentation process within the custom clearance and theresulting severe congestion will affect the trade flow in this particular zone. Inconsistency of freight transaction documents at the cross-border also makes the transaction procedure more complicated and affects the performance of the manufacturer’s competitiveness. Thus, this paper explores the current issues at the borders involving Thailand-Malaysia-Singapore. This paper also initiates to figure out the challenges and some key success factors in modelling efficiency for cross-border transactions amongst these countries. A qualitative approach has been adapted to answer the proposed research questions. The initial results stressed that congestion, thorough and repetitious documentation procedures, involvement of many documents, as well as the time-consuming clearance of documents are key issues encountered during cross-border freight movement. This situation has caused several issues such as delays in freight delivery, losses in tax collection due to delays, reluctance to share information, and effects on the competitiveness of the freight supply chain. Development in infrastructure, information sharing, regulations, logistics performance, and customs clearance procedure can overcome the problems during cross-border Thailand-Malaysia-Singapore activities. The model outcome is expected to be smoother for the administrative process during customs clearance and it is expected to be able to efficiently reduce costs.